Emotions, motivation and self-regulation in boys' and girls' learning mathematics - Cirila Peklaj; Sonja Pečjak (Psihološka Obzorja, 2011)
The purpose of our study was to investigate the relationship of affective and motivational processes and self-regulation in mathematics in secondary school students. We were interested in finding out if these relationships differ between boys and girls. Second, we predicted the use of cognitive and metacognitive strategies from emotional and motivational variables. A total of 397 students (145 boys and 252 girls) attending the first year of grammar schools in Slovenia participated in the study. Emotions were measured with the three scales assessing students' positive and negative emotions during math classes, during learning math at home and during math tests. Students' goal orientations were measured by Achievement Goal Questionnaire Revised (AGQ-revised; Elliot & Murayama, 2008), self-efficacy by Patterns of Adaptive Learning Scales (PALS; Midgley et al., 2000) and cognitive and metacognititve strategies by Motivated Strategies for Learning Questionnaire (MSLQ; Pintrich et al., 1991). More significant correlations between emotional and motivational dimensions were found for girls than for boys. The opposite was true for the relationship between emotional dimensions and strategies. Further hierarchical regression analyses showed that emotions explained a greater amount of variance in using cognitive and metacognitive strategies in boys than in girls. In both genders, positive emotions during learning math at home and math test are the best predictors of (meta)cognitive strategy use. Among motivational variables, only performance goal orientation explained significant amount of variance in all strategies in girls over and above emotional variables. Implications of emotional and motivational dimensions for the use of cognitive and metacognitive strategies in learning math are discussed, as well as implications for further research.